Animism, Materiality, and Museums How Do Byzantine Things Feel? - Peers, Glenn (Book collections on Project MUSE., 2021)
Byzantine art is normally explained as devotional, historical, highly intellectualized, but this book argues for an experiential necessity for a fuller, deeper, more ethical approach to this art. Written in response to an exhibition the author curated at The Menil Collection in 2013, these essays challenge us to search for novel ways to explore and interrogate the art of this distant culture. They marshal diverse disciplines-modern art, environmental theory, anthropology-to argue that Byzantine culture formed a special kind of Christian animism. While completely foreign to our world, that animism still holds important lessons for approaches to our own relations to the world. Mutual probings of subject and art, of past and present, arise in these essays-some new and some previously published-and new explanations therefore open up that will interest historians of art, museum professionals, and anyone interested in how art makes and remakes the world.